Sistem Informasi Manajemen Masjid Berbasis Web - Roro Fatikhin; Nuari Anisa Sivi; Maulana Malik Hidayatullah (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2023)
The trust of the congregation in the mosque management is greatly influenced by the quality of a transparent and accountable management system. Manual recording systems that are still widely used are often less effective in providing accurate, fast, and easily accessible data, especially related to cash flow information and mosque activity programs. This condition can cause unclear information that has an impact on the low active participation of pilgrims. This research offers a solution in the form of building a website-based mosque administration system that is adaptive and easy to use. System development is carried out through the stages of needs analysis, feature design, application implementation, and functional testing. The system built provides several main services, including managing worship schedules, recording income and expenditure in a structured manner, and reporting mosque activities in detail and real-time. Through the web platform, financial information and activity programs can be accessed more openly, thereby increasing transparency and accountability in mosque management. The results of the development show that this system is able to simplify the administrative process, speed up the presentation of information, and support the supervision of funds by pilgrims and administrators. Thus, a website-based administration system can be an effective solution to increase the trust of worshippers and encourage more active participation in mosque activities.